STUDI SISTEM INPUT/OUTPUT: PERANGKAT, INTERFACE, DAN OPTIMALISASI KINERJA KOMPUTER - Muhammad Rifki Hidayatulloh; Fierren Al-Hilal Saepul Bahri; Adila Muqtashida; Rio Gunawan; Safira Azahra (PT. Hasba Edukasi Mandiri, 2025)
The input/output (I/O) system is a crucial component in a computer architecture because it bridges the interaction between the external user/device and the processing unit. I/O devices consist of input devices (e.g. keyboards, sensors) to input data, and output devices (e.g. monitors, printers) to display processing results. The data from the input device is converted to a format that can be processed by the CPU, and then the results are passed to the output device via the I/O controller. This study discusses the definition and classification of I/O devices, types of I/O interfaces (Programmed I/O, Interrupt-Driven I/O, DMA), communication protocols, optimization strategies, and examples of implementations in embedded and cloud systems. An in-depth understanding of the relationship between input, processing, and output processes has proven to be key in improving the overall performance of a computer system.